Multidrug resistant Escherichia coli isolated at National Public Health Laboratory, Nepal - Acharya, Jyoti; Shrestha, Anjana; Rijal, Nisha; Jha, Runa; Rijal, Komal Raj; Sharma, Supriya; Banjara, Megha Raj; Ghimire, Prakash (Journal of Nepal Health Research Council, 2025)
Background: Antimicrobial resistance in Escherichia coli is mostly associated with ß-lactamases and carbapenemases enzyme production resulting in treatment challenges. This study was conducted with the aim to detect and characterize antimicrobial resistance in E. coli isolates.Methods: A cross-sectional study was conducted during 2018-2022, at National Public Health Laboratory where the clinical specimens (24636) received were processed for identification and characterization of antimicrobial resistance following conventional & advanced methods. Antibiotic susceptibility tests were performed by Modified Kirby Bauer disc diffusion and Minimum inhibitory concentrations using VITEK2 compact (Biomeriux). The isolates were tested for extended-spectrum β-lactamases and Carbapenemase production following Clinical Laboratory Standards Institute guidelines.Results: Bacterial growth was observed in 9% (2166/24636) of the specimens, of which 44% (959) were E. coli. Among the 959 E. coli isolates, 320 were reconfirmed with VITEK-MS (Biomeriux). Phenotypic multi-drug resistance was observed in 75% (240/320) of the isolates with 62% (197/320) extended-spectrum β-lactamases, 12% (39/320) AmpC-ß-lactamase, 10% (31/320) serine carbapenemases and 7% (22/320) Metallo-ß-lactamase while 3% (9/320) produced three types of enzymes. The extended-spectrum-β-lactamase producing E. coli were sensitive to Tigecycline (100%), Amikacin (92%), Imipenem (87%), and Meropenem (84%). Carbapenemase producers were sensitive to Tigecycline (100%), with 61% to Amikacin. Extensive-drug resistance was observed in 2% (7/320) of the isolates, with Colistin resistance in one.Conclusions: The findings highlight alarmingly high antimicrobial resistance in E. coli posing significant challenges in treatment. Early detection of multi-drug resistant isolates in healthcare settings is crucial to combat antimicrobial resistance.Keywords: β-lactamase; carbapenemases; extensive-drug resistance; metallo-ß-lactamase; multidrug resistance